2021
DOI: 10.15587/1729-4061.2021.224986
|View full text |Cite
|
Sign up to set email alerts
|

Development of the juice extraction equipment: physico-mathematical model of the processes

Abstract: Multifruit juicers are designed, constructed and improved to be able to process pineapples, oranges and watermelons efficiently. Little juice manufacturers need both a small and efficient device for juice extraction for being economically concurrent compared to big corporations. The authors of the represented paper aim to present the experimental device for juice extraction, its effectiveness, and functional. This device was created using the compressive and compressive shear forces conveyed by an auger convey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
1
9
1
Order By: Relevance
“…Calculation engineering schemes of equipment are provided based on calculations reflected in numerous works (Amirkhanov et al, 2019; Brazhnikova, 1973; Shamenov & Zhienbaeva, 2004; Shkoropad & Veksler, 1975; Tombaev, 1962). In the main, when choosing the designs of equipment considered their own possibilities of primary purification of safflower oil on the equipment and mechanisms, taking into account the needs of the development of production, in this regard, using the results of the study, offer engineering calculations of new centrifuge equipment (Medvedkov et al, 2021). Algorithm of calculation and programming, compiled under engineering methods of calculation of filters and sedimentation centrifuges in WINDOWS Math Soft Inc. MathCad 2000 (9.0) Rus and MATLAB 9.9 R2020b programs conducted through companies (Systems for scientific work, 2020; MATLAB program, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Calculation engineering schemes of equipment are provided based on calculations reflected in numerous works (Amirkhanov et al, 2019; Brazhnikova, 1973; Shamenov & Zhienbaeva, 2004; Shkoropad & Veksler, 1975; Tombaev, 1962). In the main, when choosing the designs of equipment considered their own possibilities of primary purification of safflower oil on the equipment and mechanisms, taking into account the needs of the development of production, in this regard, using the results of the study, offer engineering calculations of new centrifuge equipment (Medvedkov et al, 2021). Algorithm of calculation and programming, compiled under engineering methods of calculation of filters and sedimentation centrifuges in WINDOWS Math Soft Inc. MathCad 2000 (9.0) Rus and MATLAB 9.9 R2020b programs conducted through companies (Systems for scientific work, 2020; MATLAB program, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…That study showed that melon seed oil has an excellent antidiabetic effect and served as a scientific basis for the use of melon seed oils in the production of functional ingredients and food additives in the food and pharmaceutical industries [5]. Melon crops are increasingly attracting the attention of scientists and machine operators [6].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of agricultural pests in southeast Kazakhstan, including aphids, grasshoppers, and fungal pathogens, causes substantial yield losses and economic damage [27,28]. The reliance on chemical pesticides poses environmental concerns, compounded by climatic variability that complicates pest management.…”
Section: Introductionmentioning
confidence: 99%